Corrosive degradation evaluation of semi-parallel wire cables with high-density polyethylene sheath breaks. (October 2020) - Yu, Yujie; Man, Mengke; Zhao, Fengtao; Lin, Siwen; Guo, Fengqi
Highlights: Accelerated corrosion experiments of semi-parallel wire cables were conducted. Different cable dimensions, wire arrangements and HDPE sheath break modes were considered. A FE model for the failure mechanism evaluation of corroded semi-parallel wire cables was established. Corrosion extent relates to the distance from breakage and wire arrangements. Brittle strength evaluation model is applicable for corroded semi-parallel wire cables. Abstract: Previous investigations on corrosive evolutions are mainly based on the parallel wire stay cables, and related discussions on semi-parallel wire cables are limited. The semi-parallel wire cable has helical wire compositions and different wire bonding mechanisms, which may induce different corrosion degradation evolutions. In this study, the accelerated corrosion testes have been performed on semi-parallel wire cables with different high-density polyethylene sheath breaks. The corrosion evolution paths inside the cable were analyzed, and tensile loading tests were performed on corroded wires to get the degradation properties. The residual strength and failure process of corroded semi-parallel wire cables were studied with finite element methods. Due to the clamping effect from HDPE sheath and the tight wire arrangement inside the cable, the corrosive solution can hardly infiltrate to the inner layers. The corrosive extents varied significantly between wires at different layers and even between different sides of the same wire. With the corrosion distribution and mechanical properties of corroded wires, a finite element model for corroded semi-parallel wire cables was established. The helical wire composition, inter-wire contact and frictions, and the wire rupture features were all considered. Simulation results revealed that the high level of wire bonding effects in semi-parallel wire cables will induce the uneven wire force redistribution and helical shaped deformation, which effect may lead to faster strength degradation when comparing to parallel wire cables.